HISTORY OF THE ORIGIN OF TRANSLATION ACTIVITIES - Kiyаsоvа Rа’nо (Журнал иностранных языков и лингвистики, 2023)
The article examines questions related to the development of oral and, in particular, written translation in the ancient Near East. The translation is rightly considered one of the oldest forms of human activity, fulfilling an important social function and enabling people to communicate interlingually. With the emergence and development of the oldest centers of writing culture, international contacts increased, which led to the emergence of writing schools, where foreign languages ​​​​were also taught.